PENERAPAN PSAK 109 PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA KEDIRI - Haji, Verona; Nurdiwaty, Diah; Sugeng, Sugeng (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2023)
This research is motivated by an incident where an ZIS management institution in its operation cannot be sure that the record of its financial statements is in accordance with PSAK 109. This can lead to lack of public trust in ZIS instuitional manage for managing assets of muzzaki that has to be canneled to groups who are entitle to received it mustahiq (groups entitled to receive). Because this is one of the obligation of Muslims to always draw closer to Allah SWT. The purpose of this study is to analyze the application of PSAK 109 ZIS to the National Zakat Agency (BAZNAS) in Kediri City. This research uses a qualitative approach with a case study method. Technique that to collect the data is utilized by field research techniqiue and library research. The data analysis technique that used are by Miles and Huberman technique. The validity test of the finding using triangulation of data sources. From the results of this study it can be concluded that the National Amil Zakat Agency (BAZNAS) in Kediri City has not fully implemented PSAK 109 in the process of recording its financial statements.